Research on the Calculation of Equipment Processing Status in a DFA Model-Based Flexible Manufacturing Workshop for Structural Parts - Liao, Xinyu; Liao, Yinghua (International Journal of Computer Science and Information Technology, 2024)
In this paper, the flexible manufacturing workshop of structural parts is taken as the research object, and the DFA model of equipment production process is established to calculate the equipment state of CNC machining tools at any time, aiming at the problems of digitalization of workshop scheduling, state prediction of processing equipment required by intelligent production transformation and order processing progress prediction. The research process combines the two-dimensional array representation method of the workshop, the state transfer function and the remaining time matrix. Through the calculation of sample experiments, DFA model can effectively calculate the running state of each equipment in the workshop at any time, and predict the order processing progress by the number of equipment state cycles.